Travelling Europe, Travelling through Crisis: Disintegrated Journeys in Dorota Masłowska’s A Couple of Poor, Polish-Speaking Romanians and Zinnie Harris’s How To Hold Your Breath - Lachman, Michal (Porównania, 2021)
The article reflects on the issues of European social, political and ethical disintegration by looking at two plays which represent both geographic and mental migration of European citizens. Zinnie Harris’s play dramatizes a journey by an energetic businesswoman from the state of seeming success to the condition of collapse of the entire continent. Masłowska’s drama tells the story of a couple who have lost their geographic but also existential bearings after a prolonged bout of drug abuse and partying. The article aims at presenting the European continent as a space of alienated social and personal experience, as a community of people in permanent exile from both the private space and the public ideologies. The two plays offer a reflection on the condition of pre-Brexit Europe with the power of capturing representative lives of those individuals who have lost the sense of the common cause.